Gimnastika sportivnaya - Zarina, T. R. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
About the situation and results of Russian gymnastics in the years from 1996 until 2001 in international main competitions. Some words are also about the finances for these events.